PERSEBARAN KOMODITI JERUK MANIS KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - supandri supandri; febriandi febriandi (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This research aims to discuss about the distribution of sweet orange commodities in Pasaman sub-district Barat District. Methods are used in a descriptive method with a quantitative approach. The variables in this study are the level of productivity, the Marketing and spread of sweet oranges.The sample determination in the study was done using simple random methods(simple random sampling). The data collection techniques used are poll techniques.The research results are obtained through poll interviews as well as conducting research on the field in Pasaman sub-district of Pasaman Barat.The results of this research in the pattern of sweet citrus plants in Pasaman sub-district is spread evenly (Scattered),The sweet orange productivity level is 29.51 tons/th and the marketing is 11.11% Direct marketing and 88.88 indirect